Implementasi Kendali Tegangan Lup Tertutup Buck Converter dengan ArduinoMega - Masramdhani Saputra; saddani Djulihenanto; Irham Fadlika (Elposys: Jurnal Sistem Kelistrikan, 2021)
One type of power converter that is widely applied in the field of renewable energy is DC-DC Converter. In variousapplication cases, voltage control features are often required. One of the challenges is how to build a closed loop controller to control the output voltage of the DC-DC Converter. In this journal, an Arduino Mega based output voltage controller will be implemented. The type of voltage controller implemented is the PI controller with the consideration that the controller has been well-known tested and mathematically proven. The PI controller is set based on closed loop block diagram calculations with the Buck Converter as the main plant. The implementation of the PI controller on the Arduino Mega is based on the expected transient response settings. PI controller was successfully implemented in this study. The experimental results show that, the controller can maintain its voltage along with changes, both source and load voltage. Thus, it can be concluded that the Arduino Mega board can work well in closed loop applications for power converter control.